State of Siege in South Dobrogea. Action plan and instructions against attacks by Bulgarian komitadjis developed by the 9th Romanian Division command - Daniel Silviu NICULAE (Bulletin of "Carol I" National Defense University)
On December 10, 1864, at the proposal of the ruler Alexandru Ioan Cuza, was voted by the Romanian parliamentarians, the Law on Siege, a basic normative act for future regulations in the field. The first article stated that the state of siege could only be declared in the event of imminent danger to public safety and order. In the context of domestic political events that took place in 1864, regulation of the agrarian problem and electoral rights, legislative initiatives that determined the coup of May 2, 1864, the phrase safety and public order unseen in the first article of the law, it was primarily aimed at ensuring the exercise of public authority in implementing  the reforms undertaken by the government led by Mihail Kogalniceanu and implicitly protecting the population and the territory. Like an arch in time, in 1926, in peacetime, after 62 years since the vote on the Siege Law of 1864, the attacks of the Bulgarian comitages threatening the population, territory, and the exercise of state authority at the southern border imposed the extension of the provisions on the state of siege and their application by the War Council of the 9th Division.